2021
DOI: 10.1094/pdis-06-20-1268-re
|View full text |Cite
|
Sign up to set email alerts
|

Use of Chitosan and Other Natural Compounds Alone or in Different Strategies with Copper Hydroxide for Control of Grapevine Downy Mildew

Abstract: Grapevine downy mildew (GDM) is one of the most serious diseases of grapevines. Limitations for the use of copper-based products in organic agriculture according to EU Regulation EU/2002/473 and the later EU Commission Implementing Regulation 2018/1981 has promoted a search for alternatives. This 5-year field trial evaluated the effectiveness against GDM of several strategies using different chitosan-based formulations and application rates in comparison with other natural compounds, with these applied individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Romanazzi et al [27] reported the effectiveness of laminarin and Saccharomyces extracts mixtures and chitosan alone in reducing downy mildew in vineyards although to a lesser extent if compared to copper compounds. Furthermore, chitosan confirmed similar performances against P. viticola both under high and low disease pressures [28].…”
Section: Introductionmentioning
confidence: 68%
“…Romanazzi et al [27] reported the effectiveness of laminarin and Saccharomyces extracts mixtures and chitosan alone in reducing downy mildew in vineyards although to a lesser extent if compared to copper compounds. Furthermore, chitosan confirmed similar performances against P. viticola both under high and low disease pressures [28].…”
Section: Introductionmentioning
confidence: 68%
“…Moreover, at the European level, research has been promoted on alternative products to supplement or substitute cupric fungicides, focusing on natural compounds registered as plant protection products (PPP) or plant biostimulants [38]. Among the substitutes for copper in the antifungal fight in the vineyard, growing interest is observed for chitosan as it is a biocompatible, biodegradable, and non-toxic polymer molecule [39].…”
Section: Introductionmentioning
confidence: 99%
“…In some conditions basic substances were already at farm level, with a level of pest management not different than the standard. Just as example, chitosan hydrochloride was also applied in commercial conditions, in the field, and postharvest treatments, and several studies proved that it could have an effectiveness comparable to some commercial PPPs [ 42 , 48 ]. Basic substances, probably less efficient and practical to use than other active substances authorized as PPPs, are known and used by producers since decades as substitution means and have already demonstrated their effectiveness.…”
Section: Discussionmentioning
confidence: 99%